Law Enforcement Over Air Pollution to Bring about Sustainable Development Goals (SDGS): (A Case Study on Air Pollution in Palangkaraya, Central Kalimantan) - Paramitha, Vallencia Nandya; Sukardi, Sukardi (Prodi Hukum Tata Negara Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2021)
Forest fires in Indonesia have led to devastating effects on the environment and caused air pollution, and this issue needs to be addressed immediately. The involvement of law enforcers should play an essential role in such a case since they serve as the guidelines to solve environmental issues according to Law Number 32 of 2009 concerning Environmental Management and Protection. This research seeks to analyze law enforcement over air pollution resulting from forest fires and the necessity to enforce environmental law to allow for sustainable development goals (SDGs). With normative-juridical methods, this research discovered that issues such as forest fires departed from poor environmental law enforcement in Indonesia that fails to bring about significant changes for sustainable development. This weakness has lured the people in Indonesia to overlook the current law, coupled with poor supervision given by the government apparatuses, precluding the environmental law from being appropriately enforced. People's participation is required to enforce the environmental law to tackle air pollution caused by forest fires. The condition is expected to improve with the agenda of fixing existing issues, particularly the environmental problems for better sustainable development.